Praktik Pembukaan Lahan dengan Teknik Membakar oleh Masyarakat di Limboro Rambu-Rambu Kabupaten Majene - K, Qaizar (Pangale Journal of Forestry and Environment, 2022)
This study aims to identify the practice of land clearing with burning techniques by the community in Limboro Rambu-Rambu Village, Majene Regency. The research was conducted from September 2020 to June 2021. Data collection used an accidental non-probability sampling technique with 30 respondents. Data analysis was carried out using a descriptive analysis method.The results of the study showed that in Limboro Rambu-Rambu Village there were two methods of land clearing that were commonly carried out by the community, namely the burning technique or “metunu” which was a technique of burning with heaps. The second technique is the non-deposit combustion technique using fuel. The stages of the combustion process consist of 2 (two), namely the first combustion stage and the second combustion stage which is called “mokafo”.